Pengaruh Senam Lansia Dengan Brain Gym Terhadap Peningkatan Kognitif Pada Lansia - Setyawan, Eko; , Wahyuni, S.Fis., M.Kes; , Yulisna Mutia Sari, SSt.FT., M.Sc () (2015)
Gymnastics elderly in addition to having a positive impact on the improvement of organ function was also influential in enhancing immunity in the human body after the regular exercise. Fitness level was evaluated by monitoring the heart rate breaks, ie pulse rate at rest. So in order to become fitter, heart rate at rest should be decreased. Improved cognitive power can be done be done with Brain Gym. Brain Gym is a series of exercises based on simple body movements. Brain Gym is an exercise that is strung from a dynamic body movements obtained the balance of the activities that allow both hemispheres simultaneously. The method used in doing Brain Gym is the Edu-K (Educational kinosiology) or training movements that perform movements that can stimulate the whole brain to work. These methods enable the two sides of the brain and combines all the functions of the brain to improve cognitive abilities. Results of this study showed 1) the probability value below 0.05 (0.000 < 0.05), the implementation of the elderly exercisers had a noticeable effect in improving cognitive function before (pre) and after (post) carried gymnastics elderly, this result was able to prove the hypothesis to-1 in this study, 2) the probability value below 0.05 (0.032 < 0.05), the implementation of the brain Gym has a noticeable effect in improving cognitive function before (pre) and after (post) carried brain Gym, this result is able to prove 2nd hypothesis in this study, and 3) the probability value above 0.05 (0.108 > 0.05) Ho acceptable results, thus increasing cognitive function in the elderly gymnastics group has similarities with the Brain Gym group. The research results prove the hypothesis to-3 in this study. Keywords: gymnastics elderly, Brain Gym, cognitive.